2009
DOI: 10.1021/ja907363k
|View full text |Cite
|
Sign up to set email alerts
|

Oligocarbonate Molecular Transporters: Oligomerization-Based Syntheses and Cell-Penetrating Studies

Abstract: A new family of guanidinium-rich molecular transporters featuring a novel oligocarbonate backbone with 1,7-sidechain spacing is described. Conjugates can be rapidly assembled irrespective of length in a one step oligomerization strategy that can proceed with concomitant introduction of probes (or by analogy drugs). The new transporters exhibit excellent cellular entry as determined by flow cytometry and fluorescence microscopy, and the functionality of their drug delivery capabilities was confirmed by the deli… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
123
0

Year Published

2010
2010
2017
2017

Publication Types

Select...
7
2

Relationship

3
6

Authors

Journals

citations
Cited by 113 publications
(127 citation statements)
references
References 35 publications
(36 reference statements)
2
123
0
Order By: Relevance
“…As had been shown previously for the guanidinium-only carbonate oligomers, the carbonate backbone is shelf stable as a solid but, as desired for cargo release after cell entry, it hydrolyses with a half-life of about 8 h in Hepes-buffered saline (pH 7.4, 37°C) (26). We anticipated that the siRNA∶co-oligomer complexes would be similarly stable during cellular entry but subsequently degrade with the release of free siRNA.…”
Section: Resultsmentioning
confidence: 80%
See 1 more Smart Citation
“…As had been shown previously for the guanidinium-only carbonate oligomers, the carbonate backbone is shelf stable as a solid but, as desired for cargo release after cell entry, it hydrolyses with a half-life of about 8 h in Hepes-buffered saline (pH 7.4, 37°C) (26). We anticipated that the siRNA∶co-oligomer complexes would be similarly stable during cellular entry but subsequently degrade with the release of free siRNA.…”
Section: Resultsmentioning
confidence: 80%
“…We and others have since shown that these guanidinium-rich molecular transporters can enable or enhance the delivery of a variety of cargos, including small molecules, metals, imaging agents, peptides, plasmids, and proteins across biological barriers, such as cell membranes and the stratum corneum, the latter as part of a clinical trial (24,25). Recently, we developed an oligomerization strategy that generates unique guanidinium-rich homo-oligocarbonate molecular transporters in an exceptionally step-economical fashion (one to two steps) through a metal-free organocatalytic ring-opening oligomerization reaction (26). With this strategy, the length of the oligomer (degree of polymerization, DP) can be easily tuned by varying the ratio of monomer to initiator in the oligomerization step.…”
mentioning
confidence: 99%
“…Contrasting their efficacy in delivering siRNA, complexes formed with guanidinium-functionalized oligocarbonates D 4 :G 4 12 and D 13 :G 12 13 resulted in no detectable EGFP expression. Relative to the rapid self-immolative rearrangement (t 1/2 = 2 min) of CARTs, oligocarbonates 12 and 13 degrade slowly by passive hydrolysis (t 1/2 = 8-12 h) (46,49), establishing a strong correlation between transporter degradation rate and mRNA expression. Collectively, the exceptional performance of the CARTs is consistent with our initial hypothesis that endosomal escape and cytosolic mRNA release can be attributed to the rapid charge-altering transformation of cationic amines to neutral amides.…”
Section: Resultsmentioning
confidence: 99%
“…[14] Recently, various synthetic polymers with guanidinium side chains have been developed and successfully used for cellular delivery. [14,15] The mode of delivery of the cargo molecules by such a delivery vehicle has been debated, however, now it is accepted that polyelectrolyte complexes bind to cell surface proteoglycans such as heparin sulfate and are internalised by macropinocytosis. [16] In this report, we present the synthesis of a nonviral, noncationic delivery vector that not only binds to DNA by ionic interactions but also has cell surface targeting proteoglycan (HA) which could facilitate gene delivery.…”
Section: Introductionmentioning
confidence: 99%